Value of information in vendor managed supply chains - Aytekin, Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Parallel to the advances in information technologies and growing awareness of information sharing in supply chains, vendor managed inventory systems have become an opportunity in supply chain management. In this study we analyze the value of information sharing in a vendor managed supply chain with three suppliers and one retailer. These three suppliers sell different but substitutable items to the retailer. With this motivation an agent based simulation model is generated to analyze the value of information sharing, by comparing a Retailer Managed Inventory system in which there is no information sharing with a Vendor Managed Inventory system with information sharing. The generated models are used in the sensitivity analysis with the intention of observing the effect of holding cost, stock out cost, end item demand variability, lead times and order frequency on the value of information sharing. Finally, the models are embedded into a decision support system to be used for practical purposes by the supply chain managers.
Keywords: Freight and freightage -- Information technology.; Business logistics -- Information technology.